2019
DOI: 10.3847/1538-4357/ab31a5
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Cosmic Rays Modulation in the Vicinity of Corotating Interaction Regions: Observations During the Last Two Solar Minima

Abstract: Corotating interaction regions (CIRs) are responsible for short-term recurrent cosmic-ray modulation, prominent near solar minima. Using the OMNI data sets for two periods of low solar activity near the beginning and end of solar cycle 24, superposed epoch analysis was performed on the solar wind plasma features for 53 and 43 events during periods 2007-2008 and 2017-2018, respectively. Turbulent properties of the solar wind were studied using the variance method for each CIR. Power spectra have been constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…Undoubtedly, the effect of SW streams has an influence on the recurrent GCR modulation discussed above. This effect was not mentioned by Ghanbari et al (2019), who studied the turbulence properties of the SW around CIRs and suggested that the perpendicular transport is the main source of the GCR modulation around CIRs for both periods, independently of the HMF polarity. Recently, Leske et al (2019) compared the 27-day variations of GCRs and ACRs in 2007-2008 and 2016-2019 and suggested that a driver of this type variation must involve more than just the latitudinal gradient, explaining it by the fact, that even when the HCS is crossed more than once per solar rotation, the clear 27day variation still persists.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Undoubtedly, the effect of SW streams has an influence on the recurrent GCR modulation discussed above. This effect was not mentioned by Ghanbari et al (2019), who studied the turbulence properties of the SW around CIRs and suggested that the perpendicular transport is the main source of the GCR modulation around CIRs for both periods, independently of the HMF polarity. Recently, Leske et al (2019) compared the 27-day variations of GCRs and ACRs in 2007-2008 and 2016-2019 and suggested that a driver of this type variation must involve more than just the latitudinal gradient, explaining it by the fact, that even when the HCS is crossed more than once per solar rotation, the clear 27day variation still persists.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Ghanbari et al (2019) studied the turbulence properties around CIRs during the two recent solar minima, 2007-2008 and 2017-2018. They found that, similarly for both periods, the maximum of the total turbulent energy occurs half a day after the stream interface (SI), separating the fast and slow SW, with 2 times greater energy for the fast wind than for slow wind.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the relative damping of the second harmonic was stronger due to the fact that more probable was that Earth was outside the HCS once than twice or even more times during single solar rotation (Gil & Mursula 2017). Recently, Leske et al (2019) and Ghanbari et al (2019) based on ACE data, compared the 27-day variations of GCRs in the solar minima 23/24 and 24/25. Leske et al (2019) stated that the amplitude of the GCR variations is similar during the last two minima 23/24 (2007)(2008)(2009) and 24/25 (2017)(2018)(2019), nonetheless that of the anomalous cosmic ray (ACR) variations is substantially less in 2017-2019 than in the previous minimum [2007][2008][2009].…”
Section: Discussionmentioning
confidence: 99%
“…leaves the area under the influence of the dominant coronal hole or enters to it. Ghanbari et al (2019) proposed that the convection of solar wind does not play a significant role in the vicinity of CIRs and indicated that the GCR intensity is inversely proportional to the perpendicular di_usion coe_cient around CIR. Engelbrecht & Wolmarans (2020) studying values for the several heliospheric turbulence quantities significant to GCR modulation such as, magnetic variances, squared HMF magnitudes, as well as parallel and perpendicular proton mean free path at Earth as a result of the cosmic ray long-term modulation model concluded that the di_usion and drift coe_cients of GCR protons do not deviate much from each other during the previous minima.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, significant correlations between the local latitudinal gradient and the amplitude of the 27day variations have been reported [19], but since intensity variations often show a 27-day period even when the HCS is crossed twice per solar rotation, more than just the latitudinal gradient must be involved. Some studies using high time resolution find that quiet-time cosmic ray intensity decreases coincide with stream interface crossings and appear unrelated to sector boundaries [7,20], while others employing superposed epoch analysis over many years report that cosmic ray intensities peak at sector boundaries [21,22]. For both the 1975 and 1996 A>0 solar minima, Reames and Ng [3] found peak cosmic ray intensities at north-to-south (outward-to-inward polarity) HCS crossings with minima at south-to-north crossings, while the phase in the intervening A<0 minimum was unclear.…”
Section: Discussionmentioning
confidence: 99%